Effect of Carbon Content on Abrasive Impact Wear Behavior of Cr-Si-Mn Low Alloy Wear Resistant Cast Steels - Wang, Xiaodong; Chen, Yunbo; Wei, Shizhong; Zuo, Lingli; Mao, Feng (Frontiers in Materials, 2019)
The effects of carbon contents on wear resistance were investigated for Cr-Si-Mn low alloy cast steels. The abrasive impact wear behavior was also analyzed. The results showed that, with the increase of carbon content in steels, the metallographic structure partly transformed from lath martensite to acicular martensite gradually, the hardness increased and the impact toughness decreased distinctly, furthermore, wear resistant first increased and then decreased, that was mainly caused by the wear mechanism changed form plastic fatigue wear to brittle fracture wear.